The relationship between self-care agency and the acceptance of children with special needs at SLBN 1 North Bengkulu - Silvalia Rahma Pratiwi; Silvia Pratiwi (ANJANI Journal (Medical Science & Healthcare Studies), 2026)
Background: Children with special needs (CSN) require optimal care and support because they differ from typically developing children in physical, mental, intellectual, social, and emotional aspects. Parental acceptance of a child's condition is an essential factor influencing the quality of caregiving. One factor that may be associated with parental acceptance is self-care agency, defined as an individual's ability to manage themselves and fulfill their self-care needs, enabling them to cope effectively with the challenges of raising a child with special needs.  Objective: This study aimed to analyze the relationship between self-care agency and parental acceptance of children with special needs. Methods: This quantitative study employed a cross-sectional design. The study involved 70 parents of children with special needs at State Special School (SLB Negeri) 1 North Bengkulu, who were selected using a purposive sampling technique. Data were collected using the Self-Care Agency Questionnaire and the Family Acceptance Questionnaire. Data were analyzed using univariate and bivariate analyses to examine the relationship between variables at a significance level of 5%. Results: The findings revealed a significant relationship between self-care agency and parental acceptance of children with special needs (p = 0.001). Parents with higher levels of self-care agency tended to demonstrate greater acceptance of their children's condition. Conclusion: Self-care agency is significantly associated with parental acceptance of children with special needs. Strengthening parents' self-care agency may serve as an effective strategy to enhance parental acceptance, thereby promoting more adaptive and optimal caregiving for children with special needs.